Drought Preparedness in Brazil - Gutiérrez, Ana Paula A.; Engle, Nathan L.; De Nys, Erwin; Molejón, Carmen; Sávio Martins, Eduardo (Elsevier, 2014)
Large portions of Brazil's Northeast have experienced an intense and prolonged drought for the majority of 2010–2013. This drought, along with other droughts that have hit the South in recent years, has sparked a new round of discussions to improve drought policy and management at the federal and state levels. To assist with these efforts, the World Bank recently conducted a series of evaluations on national and sub-national drought preparedness measures and approaches across five country case studies. This particular article presents the Brazilian case study. The work draws from interviews with key experts and stakeholders, as well as document analyses, and focuses on preparedness measures and approaches at the national and one sub-national case; the state of Ceará. The analysis shows that although there is a rich history of drought management throughout Brazil, there are short-term and long-term gaps and opportunities on which decision makers might consider focusing to improve monitoring, forecasting, and early warning systems, vulnerability/resilience and impact assessments, and mitigation and response planning measures.